Socio-cultural competence of a present-day counselor: current prospects and future challenges - Aleksandr F. Bondarenko; Svetlana L. Fedko (Психолінгвістика, 2017)
This article presents a theoretical analysis of socio-cultural determinants which influence counseling practice both with the empirical study of stated phenomena in the professional awareness of counseling psychologists.